PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA KELAS XI - tyas, Riski wahyuning; Purwati, Heni; Ekowati, Noer Hudha; Shodiqin, Ali (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research aims to determine the effect of learning motivation on mathematics learning outcomes for class XI SMA Negeri 14 Semarang in the 2023/2024 academic year. This type of research is quantitative research. The population in this study were all class XI students at SMA Negeri 14 Semarang with a sample of class XI-2, totaling 36 students. The research instruments used in this research were learning motivation questionnaires and learning outcomes tests. The learning motivation questionnaire consists of 24 statement items, while the learning outcomes test consists of 7 questions with the main topic being scatter diagrams. The data analysis technique uses regression prerequisite tests, namely the first is a residual normality test, the second is a heteroscedasticity test, and the third is a linearity test, after the prerequisite tests are fulfilled then a regression test is carried out. Based on the results of regression calculations, it was found that there was an influence of learning motivation on learning outcomes as shown in the R Square results of 0.648 x 100% = 64.8%. Thus, learning outcomes can be influenced by learning motivation.